If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -3 + 2x = 15 Reorder the terms: -3 + 4x + 2x = 15 Combine like terms: 4x + 2x = 6x -3 + 6x = 15 Solving -3 + 6x = 15 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 6x = 15 + 3 Combine like terms: -3 + 3 = 0 0 + 6x = 15 + 3 6x = 15 + 3 Combine like terms: 15 + 3 = 18 6x = 18 Divide each side by '6'. x = 3 Simplifying x = 3
| (7!((5/7)^5)(2/7)^2)/(5!2!) | | 0.04x+x=200 | | f(x)=6/cos^2x | | 5t/13=25/39 | | 2a-a+b= | | -15t+15+9t=7t-4 | | 5r-10=2k | | y=1/3cos3x | | 5b+2a-3b= | | 3/4:2 | | (50+2x)(30+2x)-1500=425 | | 5/8÷3/4= | | (50+2x)(30+2x)-150=425 | | 5s-7/=7 | | 2/9×7/6 | | 4K+12=2k | | (50+x)(30+x)-150=425 | | a+3a-2a-2b= | | 20logx=32.5 | | 12h-15=9h | | a+5a+b= | | 6a-5a+4b= | | 3x-y=20x+2y=23 | | 8m-12=5m | | 81x^8-82x^4+1=0 | | 2X+4.5Y=10 | | (D^3-3D^2+4)x=0 | | x^2+14x+14+y^2-2y=0 | | Y=-0.7x+340 | | 8x^3-12x^2-2x+3=0eq | | 10(s-8)=-125 | | (40-x)(16-x)=340 |